Poor sleep quality is associated with impaired glucose tolerance in women after gestational diabetes. (June 2015) - Ferrari, U.; Künzel, H.; Tröndle, K.; Rottenkolber, M.; Kohn, D.; Fugmann, M.; Banning, F.; Weise, M.; Sacco, V.; Hasbargen, U.; Hutter, S.; Parhofer, K.G.; et al.
Abstract: We analyzed the association of sleep quality and glucose metabolism in women after gestational diabetes (pGDM) and in women after normoglycemic pregnancy (controls). Data during pregnancy and a visit within the first 15 months after delivery were collected from 61 pGDM and 30 controls in a prospective cohort study. This included a medical history, physical examination, questionnaires (Pittsburgh Sleep Quality Index (PSQI), and Perceived Stress Scale (PSS)), and 5-point oral glucose tolerance test with insulin measurements to determine indices of insulin sensitivity and insulin secretion. We used Spearman correlation coefficients and multivariate regression models for analysis.9.3 ± 3.2 months after delivery, pGDM had significantly higher fasting and 2 h glucose levels and lower insulin sensitivity than controls. There was no significant difference in age, BMI and sleep quality as assessed with the PSQI between the two groups. The PSQI score correlated with the ogtt-2 h plasma glucose in pGDM (δ = 0.41; p = 0.0012), but not in controls. This association was confirmed with a multivariate linear regression model with adjustment for age, BMI and months post-delivery. Perceived stress was an independent risk factor (OR 1.12; 95% CI 1.02–1.23) for impaired sleep. Our findings suggest that post-delivery sleep quality significantly influences glucose tolerance in women after GDM and that impaired sleep is associated with increased stress perception. Measures to improve of sleep quality and reduce perceived stress should therefore be tested as additional strategies to prevent progression to type 2 diabetes after GDM. Highlights: A sleep deficit in new mothers is a universal problem in women after GDM who are already predisposed to diabetes. We found that reduced sleep quality had detrimental effects on glucose metabolism in women after GDM. Impaired sleep was also associated with a higher level of perceived stress in women during the first year after birth. These findings suggest sleep quality and stress management as additional targets for diabetes prevention in women after GDM.